Incorporating Growth Performance with Youth Market Hog Shows - Chad Carr; Travis Arp (EDIS)
Florida, like many other states, has extensive youth swine exhibition programs but little to no commercial pork production. To remain relevant, the focus of these programs should be both educational and industry-applicable. By incorporating growth performance, youth swine shows can provide opportunities for education about growth performance and lean gain per day on test, and reward genetically superior animals. This 6-page fact sheet explains how such an exhibition program would work. Written by Chad Carr and Travis Arp. Published by the UF Department of Animal Sciences, January 2011.